Influência da contaminação do substrato na resistência adesiva de pinos de fibra à dentina radicular - Mesquita, Gabriela Campos (2010)
The present study was conducted to investigate two hypotheses: the first is that the bond strength between fiberglass posts and radicular dentin mediated by auto-adhesive and conventional resin cements is influenced by the time elapsed between endodontic filling and post space preparation. The second hypothesis is that the temporary cement type, the post space preparation moment (before provisionalization or after its removal) influence the bond strengths of posts fixated with two different resin cements to dentin. One hundred and sixty bovine incisors with similar age and anatomy were endodontically treated. Forty roots did not receive provisionalization and were divided into two groups (n=20) according to the time elapsed between endodontic filling and post space preparation ( immediately or after seven days) and then subdivided (n=10) according to the resin cement used to fix the posts (RelyX ARC or RelyX U100). The other 120 roots were analyzed in accordance with the following study factors: temporary cement used to fix the provisional restorations - HydroC (Calcium hydroxide based), TempBond (OZE based) e TempBond NE (ZONE based); post space preparation moment (before provisionalization or after its removal); and the type of resin cement. Cylindrical -tapered fiberglass posts (WhitePost #3) were silaneted and cemented, samples were stored in 37°C distilled water for 24h, and after that, were sectioned into six 1mm-thick slices that were evaluated by micropush-out test at a speed of 0.5 mm/min. Data were statistically analyzed using ANOVA and post hoc tests were calculated by using Tukey s multiple comparison test. Results indicated that the time elapsed between endodontic obturation and post space preparation influenced bonding. For both resin cements tested, bond strength increased when post space preparation was conducted after endodontic cement was set. Furthermore, it was shown that the use and the type of temporary cements, the post space preparation moment and the resin cement type influenced bonding. Groups temporarily cemented with TempBond NE and HydroC had their bond strength increased when post space was prepared after the removal of provisionalization. For TempBond groups, post space preparation moment was not significant for both resin cements. RelyX U100 showed higher bond strength values than RelyX ARC, and seemed to be less affected by different root regions. We could conclude that endodontic posts cementation with composite agents should be conducted after endodontic cement setting period. Self-adhesive resin cement should be preferred when luting fiber posts. The presence of temporary cement remnants jeopardizes final bonding, however eugenol demonstrated no effect on adhesion after one-week period.